ASSESSMENT OF MUTAGENIC AND ANTIMUTAGENIC EFFECTS OF HONEY FORMED BY INNOVATIVE WAY AGAINST CYCLOPHOSPHAMID INDUCED CHROMOSOMAL ABERRATIONS IN BONE MARROW CELLS - & Chechan, Farhan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The present study has been done to assess the mutagenic and antimutagenic effects of honey formed by innovative way (HW) in comparison with two honey formed by different feed sources ; nectar of flowers (HF) and sugar syrup (HS), against the cytotoxity and genotoxicity induced by cyclophosphamide (CP) in mice bone marrow cells ,which was evaluated using chromosomal aberration (CA). This search was carried out through two stages. In the first stage, mice were orally treated daily with phosphate buffer saline (PBS) as negative control group, and the other three groups were orally treated daily with two doses of the three types of honey (300 and 600 mg/kg) for 7 and 14 days in order to test the clastogenetic effects of the honey,In the second stage, interactions between the ideal dose (300 mg/kg) of each type of honey and the CP were used for 7 and 14 days in order to test the protective effects of honey formed by innovative way as compard to the other types of honey. The results of the first experiment indicated that the three types of honey has no significant clastogenetic effects on chromosomal aberrations of the bone marrow cells of treated mice. The results of the second experiment was showed that (HW) , especially at the ideal dose (300 mg/kg b.w.) exhibited a well protective and high anti-clastogenic efficiency against the genotoxic actions of the cyclophosphamide (CP) on bone marrow cells, by reduce CA frequencies.